2014
DOI: 10.1039/c3py00778b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and volume phase transition of concanavalin A-based glucose-responsive nanogels

Abstract: A glucose-responsive nanogel that can undergo reversible and rapid volume phase transitions is made of ConA interpenetrated in a poly(NIPAM) network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 61 publications
(94 reference statements)
0
49
0
Order By: Relevance
“…The <D h > values as a function of the solution pH were then normalized by a minimum hydrodynamic radius (<D h > 0,pH ) within the experimental pH window, because there was a difference of the size between pPBA-1 and pPBA-2 microgels. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Those results indicated that the pK a of the PBA groups might decrease to <7.9 (see Fig. 4a, we can see the same trend in the <D h >/<D h > 0,pH versus the solution pH curves for both microgels.…”
Section: Volume Phase Transitionmentioning
confidence: 83%
See 3 more Smart Citations
“…The <D h > values as a function of the solution pH were then normalized by a minimum hydrodynamic radius (<D h > 0,pH ) within the experimental pH window, because there was a difference of the size between pPBA-1 and pPBA-2 microgels. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Those results indicated that the pK a of the PBA groups might decrease to <7.9 (see Fig. 4a, we can see the same trend in the <D h >/<D h > 0,pH versus the solution pH curves for both microgels.…”
Section: Volume Phase Transitionmentioning
confidence: 83%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Those results indicated that the pK a of the PBA groups might decrease to <7.9 (see Fig. In order to explain the shrinkage behavior of the microgels upon adding glucose, two main factors should be considered: one is related to the formation of glucose-boronate, 39 more stable than glucose-boronic acid, 40 which would induce a shift in the ionization equilibrium, increase the fraction of the charged phenylboronate and thus the Donnan potential (as well as the better polymer-solvent affinity) that favor the microgel swelling; [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] another is related to the formation of glucose-bisboronate complexes, which involves one glucose molecule (a) (b) bound simultaneously to two boronates and brings additional cross-linking junctions that favor the microgel shrinking. It is noted that the DAEAM molecule possesses both aromatic rings and tertiary amines.…”
Section: Volume Phase Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ye et al reported a nanogel made of Con A interpenetrated in a chemically crosslinked network of poly( N ‐isopropylacrylamide) (poly(NIPAM)) . The semi‐interpenetrating‐structured nanogels can swell and become stable in less than 1 s after adding glucose over a concentration range of 50 μM to 20.0 mM at a physiological pH of 7.4.…”
Section: Glucose‐responsive Drug Deliverymentioning
confidence: 99%